Further to the Left: Stress-Induced Increase of Spatial Pseudoneglect During the COVID-19 Lockdown - Somma, Federica; Bartolomeo, Paolo; Vallone, Federica; Argiuolo, Antonietta; Cerrato, Antonio; Miglino, Orazio; Mandolesi, Laura; Zurlo, Maria Clelia; Gigliotta, Onofrio (Frontiers in Psychology, 2021)
The COVID-19 lockdown measures do impact psychological health; yet, less is known about their effect on cognitive functioning. The transactional theory of stress predicts reciprocal influences between perceived stress and cognitive performance. However, the effects of a period of stress due to social isolation on spatial cognition and exploration have been little examined. The aim of the present study was to investigate the possible effects and impact of the Covid-19 pandemic on spatial cognition tasks concerning spatial exploration and pseudoneglect, a physiological leftward bias. A right-hemisphere asymmetry for spatial attention processes crucially contributes to pseudoneglect. Other evidence indicates a predominantly right-hemisphere activity in stressful situations. We also analyzed the effects of lockdown on coping strategies, which typically show an opposite pattern of hemispheric asymmetry, favoring the left hemisphere. If so, then pseudoneglect should increase during the lockdown and be negatively correlated with the efficacy of coping strategies. One week before the start of the lockdown due to Covid-19 in Italy (T1), we had collected data from a battery of behavioral tests including tasks of peri-personal spatial cognition. During the quarantine (T2) we repeated the testing sessions with a subgroup of the same participants (47 right-handed students, mean age = 20, SD = 1.33). At both testing sessions, participants performed digitized neuropsychological tests, including a cancellation task, radial arm maze task and Raven’s advanced progressive matrices. Participants also completed a newly developed COVID-19 Student Stress Scale, based on transactional models of stress, and the COPE-NIV to assess coping orientation. The tendency to start cancellation from a left-sided item, to explore first a left-sided arm of the maze, and to choose erroneous response items on the left side of the page on Raven’s matrices, increased from T1 to T2. The degree of pseudoneglect increment positively correlated with perceived stress, and negatively correlated with Positive Attitude and Problem-Solving COPE-NIV subscales. Lockdown-related stress may have contributed to increase leftward bias during quarantine through a greater activation of the right hemisphere. On the other hand, pseudoneglect was decreased for better coping participants, perhaps as a consequence of a more balanced hemispheric activity in these individuals.